Pengembangan Alat Pencetak Arang Briket dengan Pendekatan Antropometri dan Analisis Kelayakan Investasi untuk Efisiensi Produksi Briket - Sudrajat, Angga; Satoto, Handy Febry; Widiasih, Wiwin (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Research on charcoal briquette MSMEs in Gedangan District, Sidoarjo Regency, still faces production efficiency issues due to approximately 30% of raw materials being wasted, limited molding capacity, less uniform briquette results, and less ergonomic and safe tool design. This study aims to develop a charcoal briquette molding tool based on an anthropometric approach and investment feasibility analysis. The anthropometric approach is used to improve operator comfort, safety, and work efficiency, while the investment analysis assesses the economic feasibility of the tool. The development results are expected to increase productivity, reduce waste, reduce production costs, and increase the competitiveness of MSMEs through the application of appropriate biomass-based technology.